2009
DOI: 10.1007/s00264-009-0774-5
|View full text |Cite
|
Sign up to set email alerts
|

High-flexion total knee arthroplasty: a systematic review

Abstract: This study is a systematic literature review of outcomes following total knee arthroplasty with implants specifically designed to enable increased knee flexion. English language comparative studies without date restriction were identified through a computerised literature search and bibliography review. Nine studies met the inclusion criteria representing a total of 399 high-flexion knee arthroplasties in 370 patients. Five studies reported greater flexion or range of motion; however, the methodological rigour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 51 publications
3
45
0
2
Order By: Relevance
“…However, the study comparing a single mobile bearing total knee prosthesis between the high-flexion design and the standard design reported similar results to several studies of fixed bearing design in terms of significantly improved short-term knee ROM and outcome [17]. Although several high-flexion designs of total knee prosthesis, regardless of issue on posterior cruciate ligament or motion of bearing unit, have shown better postoperative knee ROM than those with standard knee designs, a systematic review on results of high-flexion TKA [18] concluded that there was insufficient evidence to support advantages of high-flexion TKA, as many studies had inadequate methodological rigour, such as inadequate blinding, flawed participant selection, short follow-up periods and functional outcomes which lacked sensitivity.…”
Section: Discussionmentioning
confidence: 57%
“…However, the study comparing a single mobile bearing total knee prosthesis between the high-flexion design and the standard design reported similar results to several studies of fixed bearing design in terms of significantly improved short-term knee ROM and outcome [17]. Although several high-flexion designs of total knee prosthesis, regardless of issue on posterior cruciate ligament or motion of bearing unit, have shown better postoperative knee ROM than those with standard knee designs, a systematic review on results of high-flexion TKA [18] concluded that there was insufficient evidence to support advantages of high-flexion TKA, as many studies had inadequate methodological rigour, such as inadequate blinding, flawed participant selection, short follow-up periods and functional outcomes which lacked sensitivity.…”
Section: Discussionmentioning
confidence: 57%
“…We observed a mean HSS score of 91 and a mean knee flexion of 133°. However, it cannot be determined by the present study and it remains unclear whether HF designs improve clinical ROM and function more than conventional implants [14,31,33].…”
Section: Discussionmentioning
confidence: 83%
“…A recent metaanalysis by Gandhi et al concluded that HF implant designs improve the overall ROM compared with traditional implants but offer no clinical advantage in primary TKA [6]. In a systematic literature review focusing on outcomes after HF TKA, Murphy et al found that there was insufficient evidence to support the view that these new TKA designs improved ROM or functional performance [24]. This review included nine studies [1, 8,10,14,17,27,29,34,37] with 399 HF TKAs in 370 patients.…”
Section: Discussionmentioning
confidence: 97%
“…This review included nine studies [1, 8,10,14,17,27,29,34,37] with 399 HF TKAs in 370 patients. They conclude that the claims of greater flexion, ROM, and function for HF TKA reported in some of those studies were not supported due to poor study designs, short follow-up periods, inadequate blinding, and use of functional outcome measures that lacked sensitivity [24].…”
Section: Discussionmentioning
confidence: 99%